Faktor penghambat manajemen aksesibilitas pembelajaran siswa difabel di sekolah dasar inklusi - Wartomo (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
The research aims to find out the factors that hinder the accessibility management of students with disabilities in participating in learning in inclusive elementary schools. The research was conducted in the Province of the Special Region of Yogyakarta. This is considered in the Province of DIY which has organized an inclusive elementary school for students with disabilities. The research sample was 125 students with disabilities who were attending education at 25 inclusive elementary schools in four districts and one city of Yogyakarta. The research was conducted in May - October 2017. The data source was obtained directly from respondents or informants (primary data), data obtained indirectly, namely from related agencies (secondary data). Primary data includes the identity of respondents, information about inclusive school facilities and infrastructure, respondents' perceptions related to social aspects, and aspects of accessibility. In this study several data collection methods were used, including: questionnaires, documentation, structured and in-depth interviews. The data analysis used in this study is a quantitative and qualitative descriptive analysis technique. The results of the research are: (1) accessibility for students with disabilities seems to be a problem that is quite complicated and complex to be realized in inclusive elementary schools; (2) to realize accessibility for students with disabilities there are still many obstacles, very complicated and expensive because the government is very limited in making it happen; (3) the accessibility of public facilities for students with disabilities is only a matter of the good will of policy makers to implement them and the willingness in education to always oversee these policies; (4) realizing educational accessibility in inclusive elementary schools is how to restore the human dignity of minority groups including students with disabilities.